1975
DOI: 10.1073/pnas.72.7.2515
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and microbial decomposition of synthetic [14C]ligins.

Abstract: A definitive assay for microbiological and biochemical research on the biodegradation of lignin was developed using radioactive synthetic lignins specifically labeled in the side chains, aromatic rings or in the methoxyl groups. The [14C]lignins were prepared by oxidative polymerization with peroxidase and H2O2 Of specifically labeled coniferyl alcohol (4-hydroxy-3-methyoxycinnamyl alcohol). The synthetic polymers were shown by spectroscopic and chemical methods to contain the same intermonomer linkages found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
1
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(120 citation statements)
references
References 13 publications
5
113
1
1
Order By: Relevance
“…These were similar to previous estimates of total lignin turnover in other ecosystems (10e40 y; Bahri et al, 2008;Heim and Schmidt, 2007;Rasse et al, 2006), and of slow-pool mineral-associated C in this ecosystem (11e26 y; Hall et al, 2015b). Because we measured the most labile constituent of lignin, its methoxyl group (Kirk et al, 1975), our results suggest that the more recalcitrant aromatic C of lignin could persist in soils for decades because of interactions with Fe oxides. Trends in soil respiration differed from those of lignin mineralization (Fig.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…These were similar to previous estimates of total lignin turnover in other ecosystems (10e40 y; Bahri et al, 2008;Heim and Schmidt, 2007;Rasse et al, 2006), and of slow-pool mineral-associated C in this ecosystem (11e26 y; Hall et al, 2015b). Because we measured the most labile constituent of lignin, its methoxyl group (Kirk et al, 1975), our results suggest that the more recalcitrant aromatic C of lignin could persist in soils for decades because of interactions with Fe oxides. Trends in soil respiration differed from those of lignin mineralization (Fig.…”
supporting
confidence: 79%
“…A macromolecular synthetic guaiacyl lignin labeled with 13 C at the methoxyl position was produced (Kirk et al, 1975) to provide a sensitive index of mineralization. Lignin was precipitated onto ground leaf litter and gently homogenized with soils (20 mg lignin and 1000 mg soil) following Hall et al (2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of rates of degradation of the labeled lignocelluloses with rates of degradation of unlabeled detrital lignocelluloses has confirmed that biodegradation of the labeled material accurately tracks overall biodegradation of the lignin and polysaccharide components of plant material (Hodson et al 1984). Synthetic [14C]lignin, a dehydrogenative polymerizate (DHP) of conifer-y1 alcohol, was prepared by the method of Kirk et al (1975). Preparations of synthetic lignin have been widely used to test the ligninolytic potential of natural microbial populations and pure cultures of bacteria and fungi.…”
Section: Methodsmentioning
confidence: 99%
“…The final LTGA precipitate was dried, dissolved in 10 mL of 0.5 N NaOH, and the A,,, was measured. A standard curve for lignin was generated with dehydroconiferyl alcohol polymerizate synthesized from coniferyl alcohol and horseradish peroxidase by the method of Kirk et al (1975).…”
Section: Quantification Of Lignin and Soluble Phenolsmentioning
confidence: 99%